Analysis Of The Development Of The Sea Toll Information System (SITOLAUT) At PT Djakarta Lloyd Makassar Branch - Rifaldi Rifaldi; Sitti Syamsiah; Nurul Hatifah (CV. AFDIFAL MAJU BERKAH, 2026)
The development of the SITOLAUT application was carried out as an effort to improve the effectiveness of the Sitollaut application, particularly in managing cargo bookings to maintain cargo monopoly. The changes made in the latest version of the application also changed the roles of users in the application, requiring adaptation from various users such as shippers, operators, and consignees. This study aims to identify the forms of development in the SITOLAUT application and analyse the impact of its use by operators at PT. Djakarta Lloyd's Makassar branch. The research method used was a descriptive qualitative approach with data collection techniques through direct observation and interviews with operators involved in using the application. The analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the development of the Sea Toll Information System Application (SITOLAUT) has proven to bring significant changes to the work processes of operators at PT. Djakarta Lloyd (Persero) Makassar Branch. This development includes the addition of export booking features, FCL/LCL search filters, and updates to the interface display to be more systematic and easy to use. Overall, the addition and improvement of these features have a positive impact on increasing the effectiveness and efficiency of operator work. This is reflected in improvements in aspects of system quality, information quality, service quality, system usage, user satisfaction, and additional benefits felt in supporting smooth operations. However, in the initial stages of implementation, obstacles were still encountered in the form of booking process failures due to changes in the role of the consignee, which requires an adaptation process from users. These findings indicate that the success of an information system is not only determined by improvements in technical features, but also by the readiness and understanding of users in operating the updated system.